Pengaruh Content Marketing, Influencer Endorser dan Online Customer Review terhadap Purchase Intention Brand Skincare Skintific (Studi pada Konsumen Skintific) - Fadila, Siti Aminatul; Basalamah, Muhammad Ridwan; Normaladewi, Andi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study was conducted to see the influence of content marketing, influencer endorsers and online customer reviews on purchase intention for the Skintific Skincare Brand. The population in this study were Skintific consumers with a sample size of 90 people. The method used in this research is purposive sampling. The data collection technique used in this research was carried out by distributing questionnaires. To analyze the data in this research, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis and coefficient of determination were used. Hypothesis testing in this research was carried out through simultaneous tests and partial tests. All tests were carried out using the SPSS 25 tool. The research results showed that together the content marketing, influencer endorser and online customer review variables had a positive and significant influence on purchase intention. content marketing has a positive and significant influence on purchase intention. Influencer Endorsers have a positive and significant influence on purchase intention. online customer reviews have a positive and significant influence on purchase intention.  Keywords: Content marketing, Influencer Endorser, Online customer review, Purchase intention, Skintific